Projeto Formoso: impactos socioeconômicos e ambientais no município de Bom Jesus da Lapa-Ba - ROCHA, Demétrios Pascoal de Almeida (2016)
The semiarid region of northeastern Brazil, the region most affected by the drought in Brazil, coexists with the delay of underdevelopment and its consequences for centuries. Several policies have been implemented, following the theoretical line of development thinking of the world postwar economists, with the aim of reducing regional inequality front region to the humid region of northeast and south-central Brazil. All this assistance was planning and coordinating by the State. Among the actions, with reference in the world for regional promotion, irrigation was chosen for the water use of the São Francisco River Valley. Codevasf and its predecessors were responsible for the implementation of irrigation in the river Corrente Basin region, one of the selected areas as development centers in São Francisco Valley. The Formoso Project became a reality after years of study, planning and international financing the plan to promote the development of the middle region of Bom Jesus da Lapa, Bahia. This dissertation aims to analyze the irrigation and development impacts in the county seat of the region and realize the historical review of the implementation of the Formoso Project. For that split the survey in six steps for context: i) irrigation and the development of the Northeast; ii) irrigated perimeter Formoso - design, implementation and current situation; iii) Project Formoso and economic consequences of its implementation; iv) regional social impacts of Formoso Project; v) Project Formoso and environmental consequences; and, finally, the field research, vi) Formoso Project in view of their producers. With the results presented and noted, it can be concluded that the Formoso Project, despite the downgrading of official data, is one of the main vectors of development of the region, without long, represent proportional improvement in the city's quality of life of Bom Jesus da Lapa. It stands out as also conclusive effect of this work, the necessary reflection about the environmental impacts that the Formoso Project influences and is influenced.